1981
DOI: 10.1177/002580248102100106
|View full text |Cite
|
Sign up to set email alerts
|

Rape—A Comparison of Group Offences and Lone Assaults

Abstract: Using information obtained from police files, the characteristics of group rapes were compared to those of rapes involving a solitary attacker. A number of important differences emerged from which it was concluded that, whereas some assaults by individual offenders may reflect personal propensities or pathology, group rapes originate in the dynamics of youthful gangs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
90
3

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(107 citation statements)
references
References 3 publications
14
90
3
Order By: Relevance
“…Victim resistance has been reported to result in increased verbal and physical aggression (Davies, 1991), a reduction in sexual behaviour (but conversely an increase in sexual behaviour for sexual sadists), and a decrease in 'ingratiating social behaviours' (Davies, 1992, p. 191) by offenders in sexual offence series. Studies of victim resistance in rape and robbery offences report different victims using verbal protests, running away, and fi ghting offenders (Block & Skogan, 1986;Greenfi eld, 1997;Wright & West, 1991). Burgess and Holmstrom (1976) report the use of additional behaviours, such as stalling, fl attery, and bargaining, by some victims of rape.…”
Section: Situational Similarity Between Crimesmentioning
confidence: 99%
“…Victim resistance has been reported to result in increased verbal and physical aggression (Davies, 1991), a reduction in sexual behaviour (but conversely an increase in sexual behaviour for sexual sadists), and a decrease in 'ingratiating social behaviours' (Davies, 1992, p. 191) by offenders in sexual offence series. Studies of victim resistance in rape and robbery offences report different victims using verbal protests, running away, and fi ghting offenders (Block & Skogan, 1986;Greenfi eld, 1997;Wright & West, 1991). Burgess and Holmstrom (1976) report the use of additional behaviours, such as stalling, fl attery, and bargaining, by some victims of rape.…”
Section: Situational Similarity Between Crimesmentioning
confidence: 99%
“…Whilst the studies by Wright and West [1981] and Amir [1971] are useful in describing the similarities between offences, they do not clearly reveal whether, or how, offences differ. Similarly, they provide little in the way of theoretical significance to the behavioural variation in sex offending.…”
mentioning
confidence: 99%
“…Offenders' school performances are relatively weak and truancy is common (Bijleveld et al, 2007, De Wree, 2004. Not much is known about the personality characteristics of juvenile male group sexual assault offenders, and some researchers reported that their personality Group sexual offending by juvenile females 6 profiles appear average and not different from other, non-sexual offenders (De Wree, 2004, Woods, 1969, Wright & West, 1981. Sexual abuse victimization of offenders themselves is reported to be low (between six and eight per cent) (Bijleveld & Hendriks, 2003, Hauffe & Porter, 2009).…”
Section: Previous Research On Male Juvenile Group Sexual Offendersmentioning
confidence: 99%
“…This is an important gap as we know from previous research that there may be important differences between (adult) sexual offenders who act alone and sexual offenders who operate with co-offenders (Bijleveld & Hendriks, 2003;Hauffe & Porter, 2009;Wright & West, 1981) In fact, adult female sexual offenders very often co-offend. The co-offenders is usually a man, who is often their intimate partner.…”
Section: Introductionmentioning
confidence: 99%